Motivational needs, core-self-evaluations and their link with job satisfaction: Evidence from telecom sector of Pakistan - Saad Mahmood; Saman Attiq; Rauf I Azam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
Organizations increasingly realize that in order to keep existing external customer satisfied, it is essential to get employees satisfied. Main objective of this study is to analyze individual's motivational factors and their relationships with internal market orientation, and their overall relationship with employee job satisfaction. Data for this cross-sectional study is collected from 287 employees through questionnaire. The data is analyzed through structural equation modeling. The results showed direct relationship between employee's core self-evaluations and internal market orientation. Also that these constructs contribute significantly in enhancing job satisfaction. The study provides information on how personality relates with organizational efforts in contributing towards job satisfaction through internal market orientation. There are very rare studies to examine the impact of core-self-evaluation on internal market orientation practices' which further affects employee job satisfaction. Hence, it makes a contribution toward literature for both academic scholars and practitioners.
Keywords: 330; internal market orientation; employee job satisfaction; personality trait; core self-evaluations